2014
DOI: 10.1007/s00253-014-5955-5
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal properties of Hericium erinaceus and its potential to formulate novel mushroom-based pharmaceuticals

Abstract: Hericium erinaceus is an important mushroom with edible values and medicinal properties. Both the mycelium and the fruiting bodies contain many bioactive compounds with drug efficacy. Recent evidence demonstrates that it is helpful to various diseases, such as Alzheimer's disease, immunoregulatory, and many types of cancer. Furthermore, emerging pieces of evidence have shown that different active molecules in H. erinaceus have different functions on different organs in different diseases via the different mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 100 publications
1
27
0
2
Order By: Relevance
“…The mushroom is called "Yamabushitake" and "Houtou" in Japan and China, respectively. The fruiting bodies of H. erinaceum contain several bioactive substances, including aromatic compounds, diterpenoids, steroids, and polysaccharides (Jiang et al, 2014;Khan et al, 2013;Wasser, 2014). A doubleblind, placebo-controlled study showed that oral administration of dried Yamabushitake powder to Japanese subjects is effective for the treatment of mild cognitive impairment patients (n = 15) (Mori et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…The mushroom is called "Yamabushitake" and "Houtou" in Japan and China, respectively. The fruiting bodies of H. erinaceum contain several bioactive substances, including aromatic compounds, diterpenoids, steroids, and polysaccharides (Jiang et al, 2014;Khan et al, 2013;Wasser, 2014). A doubleblind, placebo-controlled study showed that oral administration of dried Yamabushitake powder to Japanese subjects is effective for the treatment of mild cognitive impairment patients (n = 15) (Mori et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Due to its edibility and functionality, the mushroom has attracted considerable attention. H. erinaceus is able to alleviate complex neurodegeneration, decrease gastric mucosal damage and significantly reduce the levels of plasma triglycerides (1). In addition, H. erinaceus possesses antioxidant activities, immunoregulatory activities and anti-cancer roles (1).…”
Section: Introductionmentioning
confidence: 99%
“…H. erinaceus is able to alleviate complex neurodegeneration, decrease gastric mucosal damage and significantly reduce the levels of plasma triglycerides (1). In addition, H. erinaceus possesses antioxidant activities, immunoregulatory activities and anti-cancer roles (1). H. erinaceus contains proteins, unsaturated fatty acids, carbohydrates and a variety of trace elements, including phosphorus, sulfur, calcium, magnesium, zinc, iron and copper (1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hericium erinaceus (also called lion's mane mushroom, HE) widely distributes in North America, Europe and Asia. The mushroom has been recognized as medical mushroom for long years, and especially popular in the traditional Chinese medicine (15,27). Recently, we also found its anti-obesity effect during menopause (14) and intake of HE altered the behavioral rhythm (10) by experiments on mice.…”
mentioning
confidence: 95%